2016
DOI: 10.1186/s12863-016-0386-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association for milk production and female fertility traits in Canadian dairy Holstein cattle

Abstract: BackgroundGenome-wide association studies (GWAS) are a powerful tool for detecting genomic regions explaining variation in phenotype. The objectives of the present study were to identify or refine the positions of genomic regions affecting milk production, milk components and fertility traits in Canadian Holstein cattle, and to use these positions to identify genes and pathways that may influence these traits.ResultSeveral QTL regions were detected for milk production (MILK), fat production (FAT), protein prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 70 publications
8
101
1
5
Order By: Relevance
“…O'Brien et al (2014) showed that r 2 values above 0.3 were required to give sufficient power in genome wide association studies (GWAS). In the current study, r 2 values above 0.2 were achieved at a distance less than 70 kb between adjacent markers, indicating that using BovineSNP50K BeadChip with marker interval 67.8 kb is inconsistent for achieving a high accuracy of genomic breeding values and Recently, high density (HD) chips have been used in GWAS (Mokry et al 2014;O'Brien et al 2014;Nayeri et al 2016) and a marker interval of 5 kb can be obtained from such SNP density provided that r 2 reaches 0.59 in taurine species (O'Brien et al 2014). Consequently, the HD chip could be more appropriate for GWAS than the 50K chip.…”
Section: Resultsmentioning
confidence: 64%
“…O'Brien et al (2014) showed that r 2 values above 0.3 were required to give sufficient power in genome wide association studies (GWAS). In the current study, r 2 values above 0.2 were achieved at a distance less than 70 kb between adjacent markers, indicating that using BovineSNP50K BeadChip with marker interval 67.8 kb is inconsistent for achieving a high accuracy of genomic breeding values and Recently, high density (HD) chips have been used in GWAS (Mokry et al 2014;O'Brien et al 2014;Nayeri et al 2016) and a marker interval of 5 kb can be obtained from such SNP density provided that r 2 reaches 0.59 in taurine species (O'Brien et al 2014). Consequently, the HD chip could be more appropriate for GWAS than the 50K chip.…”
Section: Resultsmentioning
confidence: 64%
“…For example, a QTL with a major effect on milk yield and composition has been identified on the centromeric end of the chromosome 14, and involves the DGAT1 gene [49]. Figure 2 shows a strong association of SNPs with milk production on chromosome 14 close to the DGAT1 gene in a genome-wide association study done on Canadian Holstein dairy cattle [111]. Similarly, linkage disequilibrium (LD) analysis highlighted a chromosomal region on bovine chromosome 20 harbouring the GHR gene which affects milk yield and composition [2,18,44].…”
Section: Candidate Genes Identified In the Key Tissues Through Associmentioning
confidence: 99%
“…Milk production and fertility traits are polygenic, affected by many genes and variants, each with a small effect on the observed phenotype [111,139]. GWAS studies of different production and fertility traits in dairy cattle have identified shared quantitative regions and candidate genes-regions that appear to influence multiple traits [27,56,111,127].…”
Section: Genomic Regions and Genes Affecting Multiple Traits In Dairymentioning
confidence: 99%
See 1 more Smart Citation
“…In livestock and companion animals, GWA studies have identified multiple genomic regions for health and disease related traits (Bermingham et al, 2014;Karlsson et al, 2013), fertility related traits (Nayeri et al, 2016;Schneider et al, 2015;Hoglund et al, 2014), production traits (Nayeri et al, 2016;Wolc et al, 2012) among other examples. GWA studies have also led to discovery of causative mutations for several traits in dogs and cattle as reviewed in Goddard and Hayes (2009).…”
Section: Genome-wide Association Studymentioning
confidence: 99%